DIGITAL TOOLS FOR IMPROVING THE WORK OF THE INTERNET STORE (Development Service Industry Management, 2024)
In this article, the authors summarize the essence and meaning of online trade at the current stage, specify the main functions and principles of online stores, specify their classification and main tasks. Thus, the authors determined that online trading is currently almost the only method that ensures the development of stationary trading enterprises by ensuring omnichannel, as well as the development of the online store market. The main functions of online stores are sales, customer base formation, product presentation and promotion, store promotion, hosting and analytics.Also, in the article, the authors analyzed the state of the Internet market and determined the main priorities of its development, taking into account a number of circumstances that determine the basic requirements for the functioning of its subjects.  The analysis of the Internet market showed its prospects and rapid development according to the models of world practice. World experience determines the main priority directions for the development and improvement of the efficiency of online stores. The main directions of such development are personalization of appeals to potential consumers and omnichannel communication with them. This is how SEO, targeted and teaser advertising, contextual advertising, etc. are widely used in the world.Based on the analysis, the authors proposed a number of tools for improving and increasing the efficiency of online stores in today's conditions. To improve and increase the efficiency of online stores, a toolkit is offered, which includes seven main methods: SEO, contextual advertising, teaser and banner advertising, price aggregators, social networks, chatbots and email newsletters.
Keywords: online trade; online market; online store; improvement of online stores